'A fish out of water?' The therapeutic narratives of class change. (May 2016) - Franceschelli, Michela; Evans, Karen; Schoon, Ingrid
Young people from working class backgrounds remained mostly excluded from the widening educational participation which characterised postwar Britain. Based on 20 semi-structured interviews which were part of a wider study about 'Social Participation and Identity' (2008–2009), this article explores the unusual learning trajectories of a group of working class adults born in 1958, who participated in higher education (HE) in a context where most people from the same socio-economic backgrounds did not. Drawing on Bourdieu's social theory, the findings suggest that different types of retrospective accounts were mobilised to reconcile working class habitus of origin and the perceived habitus as adults. Most research on working class and higher education focuses on the experiences of youth. By contrast, the use of retrospective accounts of adults has enabled the study to capture the implications that the educational trajectories have later in life. The authors consider these accounts a part of wider narratives that they define 'therapeutic'. Therapeutic narratives were employed to come to terms with the ambivalence produced by social mobility. Therefore, respondents were negotiating the sense of exclusion attached to class change, and the acknowledgement of the opportunities associated with a working class habitus accessing new social fields viaeducation.